Implementation of Disaster Mitigation in Kampung Siaga Disaster Village Segaran Village, Batujaya Sub-District, Karawang District - Nana Suryana Nasution, Lukmanul Hakim, Ardawi Sumarno (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Indonesia itself often occurs Flood disasters are natural disasters in areas that are flowed by many rivers, by simply speaking, the overflowing of rivers covering the earth’s settlements. The research method uses quantitative research methods which are based on survey / questionnaire activities with a closed list of questions. Quantitative data from the results of the survey / questionnaire, not on the estimates of the researcher or author but from the results of the respondents who have been provided with the answers provided. where the purpose of distributing this questionnaire is so that researchers can know more directly about community preparedness in dealing with floods.